Rapid Detection and Identification of Yersinia pestis from Food Using Immunomagnetic Separation and Pyrosequencing. (3rd October 2012) - Amoako, Kingsley K.; Shields, Michael J.; Goji, Noriko; Paquet, Chantal; Thomas, Matthew C.; Janzen, Timothy W.; Bin Kingombe, Cesar I.; Kell, Arnold J.; Hahn, Kristen R.
Abstract : Interest has recently been renewed in the possible use of Y. pestis, the causative agent of plague, as a biological weapon by terrorists. The vulnerability of food to intentional contamination coupled with reports of humans having acquired plague through eating infected animals that were not adequately cooked or handling of meat from infected animals makes the possible use of Y. pestis in a foodborne bioterrorism attack a reality. Rapid, efficient food sample preparation and detection systems that will help overcome the problem associated with the complexity of the different matrices and also remove any ambiguity in results will enable rapid informed decisions to be made regarding contamination of food with biothreat agents. We have developed a rapid detection assay that combines the use of immunomagnetic separation and pyrosequencing in generating results for the unambiguous identification of Y. pestis from milk (0.9 CFU/mL), bagged salad (1.6 CFU/g), and processed meat (10 CFU/g). The low detection limits demonstrated in this assay provide a novel tool for the rapid detection and confirmation of Y. pestis in food without the need for enrichment. The combined use of the i CropTheBug system and pyrosequencing for efficient capture and detection of Y. pestis is novel and has potential applications in food biodefence.